Izbrani procesnopravni vidiki sodnikove oblasti in odgovornosti v slovenski ter nemški procesnopravni ureditvi - Grm, Urška (Podjetje in delo, 2015)
Relationships between the parties to the proceedings represent an important aspect of understanding modern civil procedure regulation today. Recent reform efforts of the German legislature, which increasingly inspires the Slovenian legislator, aim to emphasize the active role of the judge. The development trend of the judicial function focuses on incentivising the parties of the proceedings to execute the necessary procedural acts effectively and without undue delay. The article aims to present the question of the limits of a judge's explanatory power and responsibility in civil proceedings, i.e. what is the minimum necessary requirement of the judge's activity in the selected procedural situations. In the Slovenian legal order, it is important to differentiate between the statutory duty of such activity during the exercise of material procedural management and the constitutional requirement, in accordance with which the judge is obliged to ensure and respect the right of the parties to be heard. The article further aims to confirm the thesis that the current procedural regulation requires the judge to actively manage and promote the procedural activity of the parties and take efforts to speed up the process. Finally, the analysis is focused on the confirmation of the view that despite the parties' satisfying the condition of "sufficient (necessary) due diligence", this should not imply that the burden and responsibility for the outcome of the procedure is deferred to the judge, whereby the parties would be (always) provided with the judge's inciting the relevant claims and evidentiary proposals.
Keywords: odgovornost; pooblastila; pravdni postopek; procesno pravo; sodni postopek; sodniki